Developing alerting thresholds for prospective drug safety monitoring. Issue 7 (24th November 2015) - Wangge, Grace; Schneeweiss, Sebastian; Glynn, Robert J.; Gagne, Joshua J.
Abstract: Background: Current methods for prospective drug safety monitoring focus on determining whether and when to generate safety alerts indicating that a new drug may be less safe than a comparator. Approaches are needed to develop safety thresholds that can be used to define whether a new drug is no less than or equally safe as the comparator. Objectives: Our aim is to develop a framework for determining which safety statements can be made about a new drug and when they can be made during prospective monitoring. Methods: We developed a two‐pronged approach to establish safety thresholds for active monitoring. First, we adapted concepts from setting margins in non‐inferiority (NI) trials ("NI approach"). Second, we summarized NI margins used in published randomized trials and reviewed publicly available data from the US FDA's website to identify the type and magnitude of evidence used in regulatory decisions involving withdrawals and black box warnings between 2009 and 2013 ("benchmark approach"). We applied the framework to a case study of dabigatran versus warfarin and major bleed. Results: We provide formulas on both risk ratio and risk difference scales for the NI approach that are analogous to threshold setting in NI trials but based on point estimates and using a maximum tolerable increase rather than a preservation factor. Using this approach, we established a safety threshold for the dabigatran case study that was within range of the findings from the benchmark approach (1.18 to 7.30). Comparing the safety threshold with post‐approval studies of dabigatran versus warfarin indicated that no safety statement can be made. Conclusions: The proposed framework expands the safety statements that can be made in current prospective drug safety monitoring systems. Copyright © 2015 John Wiley & Sons, Ltd.